Comparative Study of Five CMS System of India Mustard (Brassica juncea) with their maintainer, Based on floral Biological Characters - R. Sutar1; B.B. Mangle1, *Prem Kumar Gautam1, R.K.S. Rathore2, A. (International Multidisciplinary Research Journal, 2011)
The freshly Opened flowers were randomly chosen from the main shoot of each of the male sterile system and their maintainer at time when entire line was in full bloom. On critical observation following deformities were recorded in male sterile flowers of five male sterility systems In general all the male sterile line were late in flowering and with smaller flowers in comparison to their maintainer. On comparison of flowers parts as petal, anthers, stamins and carpel length was found that the male sterile lines were smaller than their maintained.Ã‚Â